A study of form and content of bracelets from the Textile Museum collections / Nor Amizah Abd Jamil, Arba'iyah Ab. Aziz and Mohamad Kamal Abd. Aziz - Abd Jamil, Nor Amizah; Ab. Aziz, Arba'iyah Ab. Aziz; Abd. Aziz, Mohamad Kamal (Faculty of Art and Design, 2022)
Bracelets have been important items of adornment among Malaysians, especially for women. From the time of the Melaka Sultanate and many centuries before that, bracelets have become one of the essential pieces of jewelry to be worn. There are many types of bracelets with a variety of names. The focus of this study is on bracelets. There were 7 bracelets used as a study material collected from the Textile Museum. The lack of resources and collections available in the museums was the main problem of the study. The main objective is to identify and categorize the motifs of the bracelets. A qualitative method was used. The primary data was obtained through observation and interviews while the secondary data included photographs and writing materials. The results indicated different categories of motifs. The collection of the data was analyzed according to motifs and subject matters. The motifs of the bracelets were from flora, fauna, geometric, organic, and nature. Most of the bracelets were decorated with numerous repeated motifs. This study can be continued by pursuing more in-depth on the bracelets from the aspect of their motifs and their relationship with the meaning of the motif.